Multiple Sclerosis Progression Discussion Tool Usability and Usefulness in Clinical Practice: Cross-sectional, Web-Based Survey - Ziemssen, Tjalf; Giovannoni, Gavin; Alvarez, Enrique; Bhan, Virender; Hersh, Carrie; Hoffmann, Olaf; Oreja-Guevara, Celia; Robles-Cedeño, Rene R; Trojano, Maria; Vermersch, Patrick; Dobay, Pamela; Khwaja, Mudeer; et al. (Journal of medical Internet research, 2021)
Background: A digital tool, Multiple Sclerosis Progression Discussion Tool (MSProDiscuss), was developed to facilitate discussions between health care professionals (HCPs) and patients in evaluating early, subtle signs of multiple sclerosis (MS) disease progression. Objective: The aim of this study is to report the findings on the usability and usefulness of MSProDiscuss in a real-world clinical setting. Methods: In this cross-sectional, web-based survey, HCPs across 34 countries completed an initial individual questionnaire (comprising 7 questions on comprehensibility, usability, and usefulness after using MSProDiscuss during each patient consultation) and a final questionnaire (comprising 13 questions on comprehensibility, usability, usefulness, and integration and adoption into clinical practice to capture the HCPs’ overall experience of using the tool). The responses were provided on a 5-point Likert scale. All analyses were descriptive, and no statistical comparisons were made. Results: In total, 301 HCPs tested the tool in 6974 people with MS, of whom 77% (5370/6974) had relapsing-remitting MS, including those suspected to be transitioning to secondary progressive MS. The time taken to complete MSProDiscuss was reported to be in the range of 1 to 4 minutes in 97.3% (6786/6974; initial) to 98.2% (269/274; final) of the cases. In 93.54% (6524/6974; initial) to 97.1% (266/274; final) of the cases, the HCPs agreed (4 or 5 on the Likert scale) that patients were able to comprehend the questions in the tool. The HCPs were willing to use the tool again in the same patient, 90.47% (6310/6974; initial) of the cases. The HCPs reported MSProDiscuss to be useful in discussing MS symptoms and their impact on daily activities (6121/6974, 87.76% initial and 252/274, 92% final) and cognitive function (5482/6974, 78.61% initial and 271/274, 79.2% final), as well as in discussing progression in general (6102/6974, 87.49% initial and 246/274, 89.8% final). While completing the final questionnaire, 94.9% (260/274) of the HCPs agreed that the questions were similar to those asked in regular consultation, and the tool helped to better understand the impact of MS symptoms on daily activities (249/274, 90.9%) and cognitive function (220/274, 80.3%). Overall, 92% (252/274) of the HCPs reported that they would recommend MSProDiscuss to a colleague, and 85.8% (235/274) were willing to integrate it into their clinical practice. Conclusions: MSProDiscuss is a usable and useful tool to facilitate a physician-patient discussion on MS disease progression in daily clinical practice. Most of the HCPs agreed that the tool is easy to use and were willing to integrate MSProDiscuss into their daily clinical practice.